FBM staff achievements - UiTM, Faculty of Business and Management (UiTM, 2023)
This section highlights the international achievements of FBM students and staff who participated in global exchange and collaboration programs. These initiatives, such as the Sakura Science Exchange Program and the Global Undergraduate Exchange Program (Global UGRAD), promote academic excellence, cultural exchange, and global networking opportunities.